Extended Field Efforts to Reduce the Risk of Non-response Bias: Have the Effects Changed over Time? Can Weighting Achieve the Same Effects?. Issue 1 (January 2013) - Hall, Julia; Brown, Victoria; Nicolaas, Gerry; Lynn, Peter
We examine the effects on survey estimates of extended interviewer efforts to gain survey response, including refusal conversion attempts and attempts to make contact with difficult-to-contact sample members. Previous research on this topic has identified that extended efforts do appear to affect estimates, and in ways that seem consistent with bias reduction. We extend the previous research in three ways. First, we provide the first study of changes over time in the effects of extended efforts on estimates. We study change in the UK over a ten-year period. Second, we use a more precise measure of the difficulty of contact and third, we assess the effects of extended efforts conditional on weight adjustments for non-response estimates as well as on unweighted sample statistics.